2009
DOI: 10.1007/s00221-009-1989-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walking in a force field for varying durations on aftereffects and on next day performance

Abstract: This study investigated the effects of walking in an elastic force field (FF) for varying durations (49-1,629 strides) on: (a) the magnitude and duration of aftereffects, (b) performance in the FF on the next day. On day 1 in the FF, subjects (n = 17) showed an initial large error in peak toe velocity during swing (9-61% above baseline) that was largely reduced within the first 40 strides. After FF removal, subjects (16/17) showed aftereffects: (1) reduction in toe velocity (9-38% below baseline), (2) increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Prisms cause locomotor trajectory to deviate in the direction of the prism shift, which adapts over repeated attempts (Kennedy et al 2003;Michel et al 2008;Morton and Bastian 2004). In addition to prism adaptation, studies have shown that the nervous system can adapt to imposed constraints on the walking pattern through the use of a split-belt treadmill to decouple the two limb speeds (Choi and Bastian 2007) or a force applied to the foot or leg during treadmill walking Fortin et al 2009;Savin et al 2010). Taken together, these results support the notion that the nervous system is capable of adapting to altered constraints during locomotion.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Prisms cause locomotor trajectory to deviate in the direction of the prism shift, which adapts over repeated attempts (Kennedy et al 2003;Michel et al 2008;Morton and Bastian 2004). In addition to prism adaptation, studies have shown that the nervous system can adapt to imposed constraints on the walking pattern through the use of a split-belt treadmill to decouple the two limb speeds (Choi and Bastian 2007) or a force applied to the foot or leg during treadmill walking Fortin et al 2009;Savin et al 2010). Taken together, these results support the notion that the nervous system is capable of adapting to altered constraints during locomotion.…”
supporting
confidence: 54%
“…In recent years, the notion of an internal model has been studied extensively for reaching and throwing actions using manipulations of vision and/or limb dynamics (Martin et al 1996a,b;Miall et al 2007;Shadmehr et al 2010;Shadmehr and Mussa-Ivaldi 1994), whereas a limited focus on locomotion has concentrated primarily on manipulations of limb dynamics Choi and Bastian 2007;Fortin et al 2009;Lam et al 2006;Lam and Dietz 2004;Savin et al 2010). For instance, Blanchette and Bouyer (2009) reported that subjects can adapt to an elastic force field applied to the foot during treadmill walking and show negative aftereffects in foot velocity and hamstrings muscle activity following its removal.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained alterations in the movement environment can also mediate longer-term locomotor adaptations via feedback-error learning (recalibration of motor commands based on changes in sensory feedback) [22][23]. Several studies have shown that sustained (several minutes) exposure to forces that resist lower-limb flexion during walking (e.g., using robotic devices or attaching weights around the leg) lead to changes in the locomotor command that are revealed in the aftereffects (e.g., high stepping) that are observed as soon as the forces are removed [24][25][26][27][28][29]. The presence of aftereffects suggests the formation of anticipatory locomotor commands in response to the resistance and is an example of how feedback-error learning can be used to enable locomotor adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Significant increases in overground walking speed were observed following training, but no differences were found between resistance and assistance training [33]. Given that resistance training enables specific aftereffects in the dynamic control of the swing phase [24][25][26][27][28][29], it is possible that simple tests of overground walking speed may not adequately capture the particular advantages of this approach to locomotor training, i.e., walking tasks where the dynamic control of leg flexion is particularly important (such as stepping over an obstacle).…”
Section: Introductionmentioning
confidence: 99%
“…Fortin et al (2009) provided a variety of walking environments to healthy subjects using elastic bands on a treadmill to study the alteration of lower limb muscle activity patterns. According to the results, 50 or more steps were sufficient to maintain a modified muscle activity pattern; thus, the researchers suggested that movement errors would decrease for 24 hours after initial exposure to a novel environment.…”
Section: Discussionmentioning
confidence: 99%